Strategi PT Pelabuhan Indonesia III (Persero) dalam Pengembangan Pelabuhan Benoa sebagai Cruise Turn Around Port - Kenaka Yoga Iswara, I Nyoman Gede Danendra (Jurnal Bisnis dan Keuangan, 2019)
Sea transportation has an important role in economic growth in each country, including Indonesia. As a maritime country, sea transportation has a strategic role in improving people?s welfare through the distribution of goods and passengers between islands. Nominally, goods are the major contributors to the revenues of PT Pelindo III (Persero). Goods compared, the passenger?s segment only accounts for around 0.74% of total revenue. Nevertheless, PT Pelindo III (Persero) gives special remark to international passengers with the development of Benoa Port as a cruise turn around port. This is due to the high traffic of cruise ships or international passenger ships visiting the port over the past 5 years. Meanwhile, this cruise ship visit helped boost the velocity of money in the Bali region as well as creating a domino effect for the surrounding community. This research is a qualitative research and uses in-depth interviews with 6 informants. 4 people from the internal and 2 from customers? side. The research uses Porter?s Five Forces in analyzing PT Pelindo III (Persero) as well as output in the form of an appropriate strategy proposal in the development of Benoa Port. The results of the study show that PT Pelindo III (Persero) needs to 1) Improve work culture, 2) Restructuring and regenerating human capital, 3) Cooperation and synergy of SOEs, 4) Improving service levels, 5) Optimizing facilities and 6) Setting reasonable tariffs.